2019
DOI: 10.1002/mus.26764
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and efficient scale to assess upper motor neuron disease burden in amyotrophic lateral sclerosis

Abstract: Background Validation of biomarkers of upper motor neuron (UMN) impairment in amyotrophic lateral sclerosis (ALS) requires a reliable clinical assessment of UMN findings. The Penn Upper Motor Neuron Score© (PUMNS) is a standardized measure of UMN signs in ALS. Our aims were to evaluate its intra‐ and inter‐rater reliability, and to examine inter‐item reliability as a proxy for item relatedness and scale efficiency. Methods Study procedures were performed during routine clinic visits. We calculated intra and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 9 publications
2
47
0
Order By: Relevance
“…This method proved to be effective. (19) A validation study has shown excellent inter-rater and intra-rater reliability (14).…”
Section: The Penn Upper Motor Neuron Score #mentioning
confidence: 99%
See 2 more Smart Citations
“…This method proved to be effective. (19) A validation study has shown excellent inter-rater and intra-rater reliability (14).…”
Section: The Penn Upper Motor Neuron Score #mentioning
confidence: 99%
“…Scales using clinical examination findings to grade the upper motor neuron burden (UMNB) have been used in several imaging studies for ALS (8)(9)(10)(11). These scales typically are heavily weighted toward measures of hyperreflexia, but may include measures of muscle tone or movement speed (9,(12)(13)(14). Recently one such scale that includes several types of UMN measures, the Penn Upper Motor Neuron Score # (PUMNS), underwent testing to validate its reliability (14).…”
Section: Scales To Quantify Upper Motor Neuron Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary clinical information is presented Fig. 1 ., where the ALS functional rating scale (ALSFRS-r) and Penn UMN sub-scale profile of each PLS group are additionally presented [ 13 , 14 ]. Raw grey and white matter data are also presented in box plots for each cohort in Fig.…”
Section: Data Descriptionmentioning
confidence: 99%
“…13,14 The Penn UMN (PUMN) scale is a comprehensive clinical rating scale that summates three separate subscales (CNS-Lability Scale [CNS-LS], modified Ashworth, and reflexes) to measure the UMN dysfunction manifestations of spasticity, hyperreflexia, and pseudobulbar affect in ALS. 15 Quinn et al 16 completed a study to understand the test-retest reliability of the reflexes and spasticity subdomains of the PUMN scale in 15 participants with ALS. This builds on prior knowledge that the CNS-LS subscale has good reliability by itself.…”
mentioning
confidence: 99%